2001
DOI: 10.1046/j.1365-2141.2001.02699.x
|View full text |Cite
|
Sign up to set email alerts
|

The clinical features, risk factors and outcome of thrombotic thrombocytopenic purpura occurring after bone marrow transplantation

Abstract: Summary. In this study, we retrospectively analysed the clinical features, risk factors and outcome of 22 patients with thrombotic thrombocytopenic purpura (TTP) occurring after allogeneic stem cell transplantation. All but two of these patients received stem cells from unrelated donors (UDs), two-thirds were female, three-quarters were adults and leukaemia was the major reason for transplant. The incidence of TTP was 20 out of 332 patients (6%) with UD transplants and two out of 104 recipients (2%) of matched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
136
4
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(151 citation statements)
references
References 14 publications
8
136
4
3
Order By: Relevance
“…33 The higher risk of TAM observed among female patients has also been observed in other studies. 6,11,12,16 This present study confirms this gender effect but the pathophysiology remains unresolved, hypotheses include a role of hormones, oral contraceptives, sensitization by pregnancy or other hitherto unknown factors. The increased risk for TAM was only observed with female patients, whereas stem cell transplants from female donors were not associated with a higher risk for TAM suggesting that it is not an effect of the donor stem cells, but rather of the host environment.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…33 The higher risk of TAM observed among female patients has also been observed in other studies. 6,11,12,16 This present study confirms this gender effect but the pathophysiology remains unresolved, hypotheses include a role of hormones, oral contraceptives, sensitization by pregnancy or other hitherto unknown factors. The increased risk for TAM was only observed with female patients, whereas stem cell transplants from female donors were not associated with a higher risk for TAM suggesting that it is not an effect of the donor stem cells, but rather of the host environment.…”
Section: Discussionsupporting
confidence: 75%
“…16 We did not find more TAM in recent years nor with use of peripheral stem cells. Peripheral stem cells have been shown to be associated with more chronic but not with more aGvHD, and TAM is generally an early event after HSCT.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…However, recent publications have suggested that PE has limited efficacy in treatment of TA-TMA, with relatively low response rates (20-50%) in comparison to idiopathic TTP (75%) generally reported. 2,3,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] This overall poor response to PE in TA-TMA is not necessarily surprising in light of recent insights into its pathogenesis, which suggest that TA-TMA is, in fact, a multifactorial disorder resulting from endothelial cell dysfunction secondary to a variety of insults, including immunosuppressive medications, GVHD and (especially viral) infection. 2,3,8 Unlike idiopathic TTP, TA-TMA has only rarely been associated with severe deficiency of the plasma protease ADAMTS13.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] This uncertainty in diagnosis has led to wide variations in the reported incidence of TA-TMA, a lack of consensus regarding clinical approach to management, and poor understanding of prognostic factors with respect to therapeutic response and survival. [1][2][3][4][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] To address this issue of diagnostic clinical uncertainty, two new diagnostic criteria for TA-TMA have recently been proposed; the Bone Marrow Transplant Clinical Trials Network (BMT-CTN) and the IWG (International Working Group) TA-TMA criteria. 24,25 However, neither criterion has been rigorously evaluated clinically, and issues remain with respect to the diagnostic sensitivity of both.…”
Section: Introductionmentioning
confidence: 99%